Carbeto de molibdênio promovido por níquel como catalisador na reação de reforma seca do metano - Oliveira, Peter Monnerat Celes Rodrigues de (2016)
The main objective of this work was to evaluate the promoting effect of nickel in the molybdenum carbide used as catalysts in the dry reforming of methane (DRM), tested in the temperature range of 700-850 °C. Several oxide precursors (nanostructured or not) were synthesized by the methods of coprecipitation (CP), wet impregnation and mechanical mixture in order to achieve the Ni/Mo molar ratio of 0.2. These oxides were carburized to synthetize the catalysts. The precursors and catalysts were characterized by X-ray diffraction (XRD), temperature-programmed carburization (TPC), scanning and transmission electron microscopy (SEM and TEM), N2 physisorption, CO chemisorption, temperature-programmed surface reaction (TPSR) and Raman spectroscopy. The catalysts evaluations showed that the nanostructured β-Mo2C morphology is more resistant to deactivation than the not nanostructured one. Furthermore, the CP method resulted in the most active and stable catalyst (Ni0,2MoCx), performing conversions of CH4 and CO2 of about 80 and 90%, respectively, as well as a H2/CO ratio of 0,78 during 20 h of reaction at 850 °C, due to the greater contact between the Ni0 and β-Mo2C.